A predictive scheme to assess the outcome of IVF/ICSI cycles in poor responders: an observational study in Egypt. Issue 3 (August 2016) - El Nassery, Noura; Fouad, Mona
Abstract : Introduction: In developing countries where the cost of IVF/intracytoplasmic sperm injection cycles is relatively high, the need to predict the outcome of the cycles becomes crucial, especially in cases of expected poor response. Thus, in this study we aimed to set up a scheme to predict the outcomes of IVF in poor responders. Materials and methods: This observational cohort multicenter study included 928 poor responders according to the Bologna criteria. They were divided into two groups: group I (poor responders <35 years) and group II (poor responders>35 years). The main outcome were the number of MII retrieved, the number of oocytes fertilized, the number of good quality embryos obtained, and the clinical pregnancy rates. Results: Irrespective of age, subgroups with antral follicular count (AFC) greater than 5 gave statistically more MII oocytes and number of fertilized oocytes compared with the other two subgroups. As regards the clinical pregnancy rate in group II (age>35 years), the subgroup with AFC less than 5 showed significantly lower rates when compared with the rest of the subgroups( P =0.003, P <0.001, and P= 0.006). Conclusion: In developing countries, where the cost of IVF/intracytoplasmic sperm injection is quite a burden, especially in poor responders, the age and AFC must be first assessed, and routine anti-Mullerian hormone assessment is recommended as an additional predictor to the outcome in older women with low AFC, to provide proper counseling (Clinical trials: NCT02351193).